Reaction time and mortality from the major causes of death: the NHANES-III study. - Gareth Hagger-Johnson; Ian J Deary; Carolyn A Davies; Alexander Weiss; G David Batty (PLoS ONE)
Objective Studies examining the relation of information processing speed, as measured by reaction time, with mortality are scarce. We explored these associations in a representative sample of the US population. Methods Participants were 5,134 adults (2,342 men) aged 20-59 years from the Third National Health and Nutrition Examination Survey (NHANES III, 1988-94). Results Adjusted for age, sex, and ethnic minority status, a 1 SD slower reaction time was associated with a raised risk of mortality from all-causes (HR = 1.25, 95% CI 1.12, 1.39) and cardiovascular disease (CVD) (HR = 1.36, 95% CI 1.17, 1.58). Having 1 SD more variable reaction time was also associated with greater risk of all-cause (HR = 1.36, 95% CI 1.19, 1.55) and CVD (HR = 1.50, 95% CI 1.33, 1.70) mortality. No associations were observed for cancer mortality. The magnitude of the relationships was comparable in size to established risk factors in this dataset, such as smoking. Interpretation Alongside better-established risk factors, reaction time is associated with increased risk of premature death and cardiovascular disease. It is a candidate risk factor for all-cause and cause-specific mortality.